GAMBARAN PENGETAHUAN TENTANG MENSTRUASI SISWI KELAS IV-VI MI TERPADU TAHFIDZHUL QUR’AN AL MA’SHUM - Nur Safiah; Rufidah Maulina; Iffah Indri Kusmawati; Angesti Nugraheni; Ika Sumiyarsi Sukamto (Universitas Sebelas Maret, 2024)
Lack of knowledge about menstruation can lead to unpreparedness among adolescents in dealing with it. Many young girls are unaware of the impacts following menstruation, such as the maturation of female reproductive organs, fertility levels, and the fact that, sexually, women are ready to have offspring. The level of knowledge of a young girl can influence her readiness to face menstruation. The aim of this study is to determine the level of knowledge of female elementary school students about menstruation. This research employs a descriptive quantitative method, with a population of 61 and a sample size of 34, using Total Sampling technique. Data collection was carried out through questionnaires with univariate analysis. The results of this study show that 24 students (70.6%) of Integrated Islamic Elementary School Tahfizhul Qur'an Al Ma'shum in grades 4, 5, and 6 have good knowledge about menstruation, 7 students (20.6%) have sufficient knowledge, and 3 students (8.8%) have poor knowledge. The majority of students in grades 4, 5, and 6 of Integrated Islamic Elementary School Tahfizhul Qur'an Al Ma'shum have good knowledge about menstruation, totaling 24 students (70.6%), with most of them being 11 years old